“Our Life Was Divided in Many Facets”:Anna Foa Yona, an Anti-Fascist Jewish Refugee in Wartime United States - Stefano Luconi (Transatlantica)
This article reconstructs the plight of Anna Foa Yona, a Jewish expatriate who escaped from Italy, along with her family, in the wake of the Fascist 1938 anti-Semitic measures. She had opposed Benito Mussolini’s regime before fleeing the country and, notwithstanding the hardships of making a living in her adoptive society, continued to get engaged in anti-Fascist activities after moving to the United States. The article uses her experience as a case study for the intertwinement between political exile and economic migration, in addition to shedding light on Jewish identity in exile.